2012
DOI: 10.1111/j.1545-5300.2012.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

We‐Talk, Communal Coping, and Cessation Success in a Couple‐Focused Intervention for Health‐Compromised Smokers

Abstract: We investigated first-person plural pronoun use (we-talk) by health-compromised smokers and their spouses as a possible implicit marker of adaptive, problem-resolving communal processes. Twenty couples in which one or both partners used tobacco despite one of them having a heart or lung problem participated in up to 10 sessions of a smoking cessation intervention designed to promote communal coping, where partners define smoking as "our" problem, rather than "your" problem or "my" problem, and take collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
159
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(184 citation statements)
references
References 39 publications
19
159
4
Order By: Relevance
“…Rohrbaugh, Shoham, Skoyen, Jensen, and Mehl (2012) found that "we-talk" in the cessation process for smokers can be a healthy indicator that the couple is coping communally. Another communication behavior, seeking support, is also characteristic of communal coping strategies as reported by Ibañez, Buck, Khatchikian, and Norris (2004) in their study of Mexican disaster survivors.…”
Section: Communal Copingmentioning
confidence: 97%
“…Rohrbaugh, Shoham, Skoyen, Jensen, and Mehl (2012) found that "we-talk" in the cessation process for smokers can be a healthy indicator that the couple is coping communally. Another communication behavior, seeking support, is also characteristic of communal coping strategies as reported by Ibañez, Buck, Khatchikian, and Norris (2004) in their study of Mexican disaster survivors.…”
Section: Communal Copingmentioning
confidence: 97%
“…Behavioral techniques, including modeling, behavioral rehearsal, positive reinforcement, and home assignments were used to teach the participant-partner pair more effective ways to express positive feelings (e.g., recognizing success, expressing gratitude), make requests (e.g., going to the gym together, help with transportation), and express negative feelings (e.g., feeling disappointed) as they related to health behavior changes. Partner communication about health behavior changes such as smoking cessation and weight loss has been the focus of prior studies in general population samples (Rohrbaugh et al 2012;Romo and Dailey 2014), and recent intervention studies have attempted to teach partners more effective ways to talk with participants about negative and positive health behaviors (Patten et al 2011;Sorkin et al 2014;McDonnell et al 2015). Equipping support partners and participants with effective communication skills for giving and receiving support for health behavior change may be a key mechanism of successful partner-support lifestyle interventions for obese individuals with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies suggest that having a communal coping orientation promotes psychological and marital adjustment [79,80], very little is known about how communal coping is actually communicated or unfolds during couples' discussions about cancer. A growing body of research suggests that, unlike self-reports of coping which are vulnerable to social desirability and other cognitive biases, speech particles like pronouns are more impervious to conscious choice [81] and may serve as an 'implicit' measure of coping focus [82]. For example, some studies have demonstrated associations between the use of first-person plural pronouns (e.g.…”
Section: How Couples Communicate Dyadic Copingmentioning
confidence: 99%